Analysis of Complications Following Distal Ankle Nerve Blocks for Foot and Ankle Procedures. Issue 1 (January 2022) - Bartholomew, Ania; Slone, Tyler; Ciesa, Michael; Cheney, Nicholas A.; Clark, Brian C.
Category: Ankle; Arthroscopy; Bunion; Hindfoot; Midfoot/Forefoot; Other Introduction/Purpose: Popliteal nerve blocks are a common procedure employed by anesthesiologists to augment intraoperative anesthesia and provide postoperative pain control. Unfortunately, these can be associated with unintended complications including pain, numbness, and foot drop, sometimes without clear resolution. Studies from Kahn (2017), Anderson (2015), Park (2018), Lauf (2020) suggest complications higher than previously reported with Lauf (2020) finding short-term complication rates of 10.1% and 4.1% long-term as confirmed by EMG. Our study looked to address the complication rates from an alternative anesthetic procedure, a distal ankle nerve block involving anesthesia to the five nerve(s) more intimately involved in the surgical procedure. This alternative technique may provide equivalent anesthetic properties and pain relief as popliteal blocks, with fewer complications for many patients across various demographics. Methods: We retrospectively reviewed patient charts and messaging from 2019 to 2021 that received a distal ankle field block for various surgical procedures including ankle arthroscopy, ankle fractures, and lateral ankle stabilizations. The five nerves anesthetized in the distal ankle nerve block included the tibial, superficial and deep peroneal, sural, and saphenous. Thus far, 61 surgeries have been reviewed and analyzed for neuropathic complications and confirmed via EMG. Results: Of the 61 patients analyzed, 3 patients were found to have a superficial peroneal neuropathy that included dorsal numbness as a result of the distal ankle block, resulting in a 4.92% complication rate. 1 patient required a rescue block to be performed postoperatively for pain. The remaining 57 patients recovered appropriately and without complications. No motor complications have been found from patients receiving distal ankle nerve blocks, as performed by the senior author. Conclusion: With the absence of motor complications and markedly reduced incidence of sensory complications, distal ankle nerve blocks may be a beneficial alternative to popliteal nerve blocks for various foot and ankle orthopedic surgeries. As motor complications can result in life-altering disability, an anesthetic procedure with reduced negative motor outcomes can improve surgery and recovery prognosis. Future directions for this study include adding more patients to increase the sample size, as well as continuing to follow current patients, monitoring symptoms or complications.